Pengembangan Pembelajaran Berbasis Steam dengan Buku Pop Up pada Kreativitas Anak Usia Dini - Sopia Wulandari; Annisa Wahyuni; Syamsiah Depalina Siregar (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
This study also aims to develop an Educational Play Tool (APE) in the form of a pop-up book, understand its characteristics, test its practicality, and ensure its effectiveness. The research method employed is Research and Development (R&D) using the ADDIE (Analyze, Design, Development, Implementation, Evaluate) development model. Data were collected through observations, interviews, and questionnaires administered to validators and educators. The results of the study indicate that: (1) The STEAM-based learning process with pop-up books developed using the ADDIE model and STEAM steps is feasible and valid for use as an instructional medium that can enhance students' creativity. (2) The characteristics of STEAM-based learning with pop-up books are simple, attractive, enjoyable, easy to use, and capable of enhancing student development. The guidebook developed also facilitates teachers in using the pop- up books. (3) The practicality of using the pop-up book is considered very valid with a percentage of 88%, while the guidebook is deemed very practical with a percentage of 90%. (4) The effectiveness of STEAM-based learning with pop-up books is proven, with a percentage score of 90%, indicating that the pop-up book is highly valid in facilitating the understanding of learning concepts for early childhood.